The usefulness of financial statement reporting by charitable companies limited by guarantee in Malaysia / Muhammad Faiz Tumiran - Tumiran, Muhammad Faiz (2013)
In Malaysia, a non-profit organization can be formed as a company under the Companies Act 1965 and must registered with the Companies Commission of Malaysia (CCM). These types of company is known as a company limited by guarantee (eLBG) whereby generally this company is established to provide a benefits for its target populations. CLBG may establish for many purpose such as sports, religion, charitable and other non-profit object. The CLBG is prohibited to be register with a share capital and this requirement basically provide a basis to classified eLBG as a public company because the CLBG is not full fill the requirement of private company as stated in section 15 of the Companies Act 1965. For this study, the research is focus on charitable company limited by guarantee because the main sources of revenue or income for the companies are derived from contributions and donations. Thus, the research will study on management of the contributions and donations based on the information from financial reports of the company. The purpose of this applied research project is primarily to scrutinize the usefulness of financial statement reporting by charitable companies limited by guarantee in Malaysia as prescribed in Companies Act 1965 as well as according to approved accounting standards which is developed by the Malaysia Accounting Standard Board (MASB). MASB is the main body to issue an approved accounting standard and to enhance the standard from time to time and the function of MASB is stated under the Financial Reporting Act 1997. The main concern of this study is whether there is limitation for the charitable company limited by guarantee to follow this standard in which, performance and accountability will be analyzed and failure to do so might affect the whole financial report. These attributions may lead to the improvement on the level of governance and accountability in order to satisfy all the relevant parties, especially the stakeholders and the public's interest as a whole. In the end of this study, several suggestion and ideas were discussed based on the findings which can be related to regulator perspective, interested party perspective and public perspective.